Influence of Eu3+ dopant on lithium barium gadolinium phosphate glass properties for orange-reddish photonic devices. (June 2023) - Kamonpha, P.; Manyum, P.; Chanthima, N.; Tariwong, Y.; Triamnak, N.; Yimnirun, R.; Rujirawat, S.; Kidkhunthod, P.; Tanthanuch, W.; Kothan, S.; Kim, H.J.; Kaewkhao, J.
Abstract: The Eu 3+ -doped lithium barium gadolinium phosphate glasses were prepared using the conventional melt-quenching method with different concentrations of Eu2 O3 and Gd2 O3 . The physical characteristics were determined by refractive index, density, molar volume, oxygen packing volume, and oxidation states. Moreover, the optical characteristics were investigated via photoluminescence spectroscopy (PL), UV-vis spectroscopy, Radioluminescence (RL), and decay time. It was found that the Gd2 O3 concentration of 12 mol% was the optimum composition for further investigations of the Eu2 O3 doping concentration optimization. The emission spectra of PL and RL showed the strongest intensity of orange-reddish emission (λEx  = 394 nm) when the Eu2 O3 concentration was at 0.3 mol% corresponding to energy transition from 5 D0 → 7 F0, 1, 2, 3, 4 . The oxidation state of Eu 3+ ions due to the formation of non-bridging oxygens (NBO) in the glass network was confirmed by using X-ray Absorption Near Edge Spectroscopy (XANE). Furthermore, the high transparency and fast decay time in the range of 2.4–2.8 ms displayed the potential to improve laser and radiation detector performances. Highlights: Europium-doped lithium barium gadolinium phosphate glass were developed. Gd2O3 and Eu2O3 concentrations were optimized. Emission and excitation spectra of Eu3+ ion show 612 nm and at 394 nm. Oxidation of Eu3+ ions of samples. XANE spectra of L3 -edge of Europium.